Carved ambers shaped as felines in the Italian Peninsula (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2022)
In this paper, we discuss pre-Roman carved ambers representing felines. There are currently 33 examples found on the Italian Peninsula, but many others are stored in foreign museums without information about their provenance. They are dated between the middle of the 7th and 4th century BC and come from Po Valley Etruria, Piceno, southern regions (present-day Puglia, Basilicata and Campania), and the Etruscan-Latial area. Outside the Peninsula, some ambers have been found in Serbia, Israel and Syria. The Italic artefacts were mostly used as pendants and sometimes covered the bow of a fibula. Iconographically, they are mainly protomes, felines in a crouching position, scenes with different animals, and other unica. The stylistic study of carved ambers shaped as felines allows us to reconstruct part of the trade routes active during the Iron Age, outlining, for example, the circulation of the same models along the Italian Adriatic shore in the 6th and 5th century BC.
Keywords: amber; Iron Age; feline; lion